FAKTOR RISIKO KEJADIAN BRONKITIS DI PUSKESMAS MEKAR KOTA KENDARI - La Ode Alifariki (Akademi Keperawatan Dharma Husada Kediri, 2019)
Bronchitis is usually often caused by viruses such as Rhinovirus, Respiratory Syncitial virus (RSV), influenza viruses, influenza viruses, and coxsackie viruses. Based on data obtained from Kendari Medical Record in Kendari City in 2016, there were 107 cases of bronchitis, and increased to 170 cases in 2017. While the number of cases of bronchitis that occurred in 2018 to June was 93 cases in Mekar Health Center recorded the incidence of bronchitis to date continues to grow. The purpose of the study was to determine the risk factors for bronchitis at Mekar Health Center in Kendari City This type of research was a case control using a retrospective design. The study population was all the people who were treated at the Mekar Health Center in Kendari City, in January - June 2017 as many as 93 cases. The research sample was 76 respondents. The sampling technique is simple random sampling. The statistical test used is Odds Ratio. The results showed that family history was a risk factor for the incidence of bronchitis (OR = 9,371), occupation was a risk factor for bronchitis (OR = 2,823), smoking history was a risk factor for bronchitis (OR = 5,769). It was recommended to hold counseling on the dangers of smoking to lung health to the public and also urge the government to curb cigarette product advertisements and increase anti-smoking campaign advertisements through various promotional media.